The sufi terms in the book “zubad kolasat ATTASSAWOF” of imam AL IZZ IBN ABD ASSALAM died in 13th century - Haddoshi, Ibrahim Nadan (Journal of Islamic Sciences, 2018)
The objective of this study is to follow the sufiterms mentioned in the book “zubadkolasat ATTASSAWOF” of imam AL IZZ IBN ABD ASSALAM who died in 13thcentury. our study is based on the fact that the Sufism is a method of refinement of ethics and self-filtering. this show that term is the essence of this method. for this we have studied the sufiterms in the context of the objectives of mystical community for being approach to the comprehension of readers who they think to Assimilate mystic science and Emotional experiences of Sufism men who they represented a linguistic community which owned ability to attract knowing its scientific linguistic and sentimental systems in order to gain virtues and high morals that humanity needs to the stabilization of order in world. After that we can concluded that sunni Sufism is a civilized method of life and a philosophy in answering to the questions posed by all people searching peace of mind and confort.